Erroneous Conduct of Foreign Policy: A Realism Analysis of US Involvement in the Vietnam War - Manullang, Abel Josafat (Universitas Sulawesi Barat, 2022)
The Vietnam War is known to be one of the longest wars the US has been involved in. Many may have associated the war as just another one of the many proxy wars the US was involved in during the Cold War. However, there is more to learn from the Vietnam War as the recent conflicts the US was involved in, like that in Afghanistan, bore a resemblance to that of the Vietnam War. Hence, to understand the current state of the US, it is important to take a thorough look into the Vietnam War. The article aims to provide explanations to the driving force behind US involvement, its flawed approaches and perception towards its conduct in Vietnam along with the state of realism after the end of the Vietnam War. The article utilizes the qualitative research method along with the realism school of thought to answer the research questions. The result shows that the national interest on power accumulation and national security considerations were the driving force behind the US involvement. Moreover, on the issue of US approaches throughout the war, the reliance on realist values can be attributed as one of the factors that led to the US failure in Vietnam. In regard to realism's fate following the end of the war, it can be seen that the current and foreign policies made after the Vietnam War are still imbued with it.